Problems That Confronted Public Works in 19th Century Philippines - Royeca, Jon (HISTORICAL: Journal of History and Social Sciences, 2025)
Acquiring government contracts in the Philippines is difficult. The entities that want to win contracts need to submit voluminous documents, while the processes are numerous and require months to complete. Such cumbersome measures are not new; they are a problem that can be traced back to the Spanish colonial rule of the Philippines (1565-1898). This paper aims to identify three problems that beset projects of the Spanish colonial government in the Philippines in the 19th century, and how those problems affected the social conditions at the time. The historical analysis method is used in this paper to examine archival records, government reports published in newspapers, and contemporary articles that can pinpoint those problems. This paper uses the online archival research procedures in gathering the needed data, such as those that can be accessed from the Portal de Archivos Españoles (Spanish Archives Portal) and the Miguel de Benavides Library and Archives of the University of Santos Tomas in Manila, as well as other writings relative to the said problems. This qualitative research also proves that many of the present predicaments are a continuation of the past, that is: the cited problems of the 19th century have not been arrested.